A case report of odontogenic cyst by CBCT analysis: a calcifying odontogenic cyst or dentigerous cyst? - Agustin, Sylvia; Adawiyah, Jumiatul; Pramanik, Farina; Ramadhan, Fahri Reza (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: Odontogenic cysts are pathologic cavities filled with fluid originating from the odontogenic epithelium remnants forming teeth. Dentigerous and calcifying odontogenic cysts are examples of cysts that form during development. Based on how they form, they are one type of odontogenic cyst. Many lesions have similar characteristics, making it challenging to differentiate them. Case Report: An oral surgeon referred a 19-year-old male patient for a CBCT radiographic examination of the maxilla, which revealed a dentigerous cyst in the patient's clinical report. The patient's overall health was delicate. An intraoral examination revealed no edema, symmetrical, painless facial structure, and no clinical signs of periodontal disease nor dental caries. A panoramic radiograph showed a multilocular, well-defined, and corticated radiolucent lesion that made teeth 11–12 and 21–23 shifted. Conclusion: Clinical and imaging variables play essential roles in the diagnosis and differential diagnosis of odontogenic cysts. CBCT radiography could be a suitable modality for diagnosing odontogenic cysts, although histopathology is the gold standard for a definitive diagnosis.